The role of nanoparticles in plant biochemical, physiological, and molecular responses under drought stress: A review - Rasheed, Adnan; Li, Huijie; Tahir, Majid M.; Mahmood, Athar; Nawaz, Muhammad; Shah, Adnan Noor; Aslam, Muhammad Talha; Negm, Sally; Moustafa, Mahmoud; Hassan, Muhammad Umair; Wu, Ziming (Frontiers in Plant Science, 2022)
Drought stress (DS) is a major challenge to sustain to global crop production and food security. Thus, it is needed to develop cost effective measures to improve the crop productivity in order to meet the needs of growing population. The use of nano-particles (NPs) has emerged as an excellent tool to improve the crop production under the current scenario of rapid climate change and global warming. The application NPs can substantially improve the plant growth and tolerance against abiotic stresses. Drought stress negatively affects plant growth, physiological, and metabolic processes and it also disturbs cellular membranes, nutrient and water uptake photosynthetic apparatus and antioxidant activities. However, DS in plants can be improved by application of NPs. The application of NPs protects the membranes, maintains water relationships and improves the nutrient and water uptake and leading to an appreciable increase in plant growth under DS. Nano-particles also protect the photosynthetic apparatus, improves photosynthetic efficiency, osmolytes, hormones and phenolics accumulation which provide the better resistance to plants against DS. Besides this, NPs also strengthens antioxidant defense system, genes expression and brings ultra-structural changes in plant body to counter the deleterious impacts of DS. Therefore, it is imperative to understand in detail about the mechanisms of NPs to induce DS tolerance in plants. Therefore, in this review we discussed the role of NPs in various plant responses to improve DS tolerance. Additionally, we also highlighted the various research gaps that must be fulfilled in future research studies.